A genuinely monumental facade: The design competition for the extension of the headquarters of de Nederlandsche Bank on Oude Turfmarkt in Amsterdam (1915-1916) (Bulletin KNOB, 2015)
In September 1915, De Nederlandsche Bank (DNB) held an invited design competition for a new building beside the bank’s existing headquarters on Oude Turfmarkt in Amsterdam. The Dutch central bank had grown so much since its founding in 1814 that expansion was unavoidable. Five architects – E. Cuypers, A.D.N. van Gendt, F.W.M. Poggenbeek, C.B. Posthumus Meyjes and J.A.G. van der Steur – were invited to submit plans. How the bank arrived at this choice of architects is unknown; in a report to the commissioners, the board stated that they had chosen five architects with a distinguished record in designing bank buildings. The archival drawings constitute a representative sample of the architectural views of these prominent, stylistically conservative architects.The board’s choice of architects indicated that it was not looking for innovative architecture; more progressive architects like H.P. Berlage, K.P.C. de Bazel and W. Kromhout were deliberately ignored. It is clear from the terms of reference that the DNB board had decided views on the design of the new street elevation that would stand alongside the existing frontage designed by W.A. Froger. The bank asked the architects to bear in mind a possible future doubling of the facade thatwould see Froger’s elevation disappear altogether. The bank required a ‘genuinely monumental facade, in harmony with the national style and in particular with the Amsterdam style’. Above all, it should not be a copy of a foreign facade, which would look out of place in the historical city. Given such ideas it is hardly surprising that the five architects came up with fairly conservative designs. Their plans demonstrate that the request for an elevation ‘in the Amsterdam style’ was open to a range of interpretations; nor were the architects equally successful in adjusting their designs to the scale of the surrounding buildings. The designs attest to the dilemma with which the bank had saddled them in asking for a design that could stand on its own but that would also prove satisfactory in the event of further expansion.We do not know which design the board preferred, but as it turned out there was no new building because the city council wanted to purchase the site on Oude Turfmarkt from the DNB for an extension of the Binnengasthuis hospital. It was not until 1967 that the DNB moved into a new headquarters building on Frederiksplein designed by M.F. Duintjer.